2013
DOI: 10.1007/s11011-013-9431-1
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic fitness and cognitive function in midlife: an association mediated by plasma insulin

Abstract: Insulin resistance in midlife increases the risk of dementia in late-life. In contrast, habitual aerobic exercise is an established strategy to ameliorate insulin resistance which may translate into better cognitive outcome. Purpose To determine the role of plasma insulin in mediating the relation between cardiorespiratory fitness and cognitive function. Methods Fifty-eight adults completed assessments of plasma insulin levels, maximal oxygen consumption (VO2max), and neuropsychological test performance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Importantly, research has indicated the mediating role of insulin resistance on the relationship between aerobic fitness and memory. That is, increased aerobic fitness may favor memory performance via decreased insulin resistance (Tarumi et al, 2013). This finding has been expanded by a study showing close relationships between increased aerobic fitness, increased insulin sensitivity, and greater cortical thickness in the frontal lobes in adolescent children, with higher insulin sensitivity showing stronger association with frontal cortical thickness (Ross et al, 2015).…”
Section: Possible Mechanismsmentioning
confidence: 92%
“…Importantly, research has indicated the mediating role of insulin resistance on the relationship between aerobic fitness and memory. That is, increased aerobic fitness may favor memory performance via decreased insulin resistance (Tarumi et al, 2013). This finding has been expanded by a study showing close relationships between increased aerobic fitness, increased insulin sensitivity, and greater cortical thickness in the frontal lobes in adolescent children, with higher insulin sensitivity showing stronger association with frontal cortical thickness (Ross et al, 2015).…”
Section: Possible Mechanismsmentioning
confidence: 92%
“…The cardiovascular benefits of aerobic exercise are well known [46] and fitness training has been associated with cognitive enhancement in nondemented older adults [47]. Our own research has demonstrated that fitness-related benefits on neuronal viability [48], cerebral perfusion [49], and cognitive function [50] are evident as early as midlife. However, it is still unclear whether this benefit is simply due to prevention of other risk factors (e.g., reductions in blood pressure), or whether exercise can reverse the negative effects of aging on the brain.…”
Section: Future Direction 1: Interventions To Preserve Brain Functionmentioning
confidence: 92%
“…Although there are fewer studies in middle age (Adamo et al., 2020; Malmstrom et al., 2005), similar associations have been demonstrated. For example, in middle age, weaker grip strength was cross‐sectionally associated with lower executive function, global cognition and verbal fluency (Adamo et al., 2020; Malmstrom et al., 2005), and lower CRF was associated with lower global cognition and memory (Tarumi et al., 2013). The mechanisms underpinning these relationships are uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…This relationship is likely driven by vascular disease (Kivipelto et al., 2005), physical inactivity and pro‐inflammatory markers released from adipose tissue (Craft, 2009). However, collectively, these studies have mainly considered strength, obesity and CRF independently (Adamo et al., 2020; Dahl et al., 2013; Malmstrom et al., 2005; Tarumi et al., 2013) and included small sample sizes ( n < 60) (Adamo et al., 2020; Tarumi et al., 2013).…”
Section: Introductionmentioning
confidence: 99%